2009
DOI: 10.1111/j.1708-8208.2008.00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diameter and Length on Stress Distribution of the Alveolar Crest around Immediate Loading Implants

Abstract: Increasing the diameter and length of the implant decreased the stress and strain on the alveolar crest, and the stress and strain values notably increased under buccolingual loading as compared with vertical loading, but diameter had a more significant effect than length to relieve the crestal stress and strain concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
83
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 24 publications
7
83
1
7
Order By: Relevance
“…The reduced peri-implant strain with large diameter implants is in agreement with several photoelastic 39) and finite element 2,9,14,15,[22][23][24][25][26][27][28] studies in which the authors reported that increasing implant diameter would result in reduction in crestal bone strains. In these studies, implants were placed in mandibular bone in anterior 14,15) , premolar 24) , and molar 2,26) positions.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The reduced peri-implant strain with large diameter implants is in agreement with several photoelastic 39) and finite element 2,9,14,15,[22][23][24][25][26][27][28] studies in which the authors reported that increasing implant diameter would result in reduction in crestal bone strains. In these studies, implants were placed in mandibular bone in anterior 14,15) , premolar 24) , and molar 2,26) positions.…”
Section: Discussionsupporting
confidence: 74%
“…Implant diameter affected stress more in cortical bone at the crest of the alveolar ridge 2) and had a more significant effect than implant length to relieve crestal stress and strain concentrations 14) . The implant diameter influence the interfacial stress levels, and the effects of changing implant diameter is significantly noticed in the cortical bone 15) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The length, diameter [6], and the roughness of the implants [7,8], as well as the associated drilling [9] are elements for achieving high insertion torque, which means good primary stability.…”
Section: Introductionmentioning
confidence: 99%